The role of the school library in teaching and learning: a case study of a public basic school in Accra, Ghana - Omenyo, Rosekel (Library and Information Studies Centre (LISC), 2017)
This study examined the role of school library in teaching and learning and sought to establish the relationship between the use of school library resources and teaching and learning in basic schools in Ghana. The study was conducted in Achimota Basic School (ABS), using the case study methods of interviews, observation, focus group discussions and document analysis. The findings revealed that students and teachers appreciate the presence and function of the school library acknowledging it as fundamental in every educational system especially at the basic school level. The findings also revealed that students and teachers actually used the library resources in site of the fact that one of the challenges facing the library was the inadequacy of its stock. It is hoped that the findings of the study will persuade the Ministry of Education and the Government of Ghana to reconsider the role of school libraries in basic schools. Recommendations are made toward improving school libraries in general and the Achimota Basic School Library in particular.